Konflik Elite Politik di Pedesaan: Relasi antara Badan Perwakilan Desa dan Pemerintah Desa - Cahyono, Heru (Jurnal Penelitian Politik, 2005)
Rurai Representative Body (Badan Perwakilan Desa) claims their institutions bring the people aspirations, but in reality BPD shows themselves as an elitist and failed to express people’s voice. Large authority that is possessed by BPD, such as suggesting the regent to dismiss the head of the village from his job, has been endorsed the grow of politicization ofBPD by its members.This new uniformity policy has caused a dilemma, because not all village in Indonesia are ready to take representative democracy model. The rule of law assumes village as an administrative units and extremely formal. It also simplificate the heterogenity or plurality of village s in Indonesia, such as ignoring the variety oflocal milieu and local condition, cultural differences, and social structure differences in society.